2005
DOI: 10.3748/wjg.v11.i31.4838
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic fatty liver, overweight and ischemic heart disease

Abstract: The presence of fatty liver and its severity should be carefully considered as independent risk factors for IHD. Results of the study suggest the synergistic effect between fatty liver and overweight for developing IHD. Abdominal sonographic examination may provide valuable information for IHD risk assessment in addition to limited report about liver status, especially for overweight males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 31 publications
6
56
0
3
Order By: Relevance
“…In both non-diabetic and type 2 diabetic individuals, those with ultrasound-diagnosed NAFLD have a higher prevalence of clinical CVD than do their non-steatotic counterparts, and this association is independent of obesity and traditional risk factors [26,29]. In patients consecutively submitted to undergo elective coronary angiography, NAFLD was correlated with a greater severity of coronary artery disease, independently of traditional risk factors and components of the metabolic syndrome [30].…”
Section: Nafld and Increased Prevalence Of Clinical Cvdmentioning
confidence: 97%
See 1 more Smart Citation
“…In both non-diabetic and type 2 diabetic individuals, those with ultrasound-diagnosed NAFLD have a higher prevalence of clinical CVD than do their non-steatotic counterparts, and this association is independent of obesity and traditional risk factors [26,29]. In patients consecutively submitted to undergo elective coronary angiography, NAFLD was correlated with a greater severity of coronary artery disease, independently of traditional risk factors and components of the metabolic syndrome [30].…”
Section: Nafld and Increased Prevalence Of Clinical Cvdmentioning
confidence: 97%
“…The main cross-sectional [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and prospective [11,[32][33][34][35][36][37][38][39][40][41][42][43] studies on the association between NAFLD and intermediate markers of CVDor clinical outcomes are shown in Tables 1 and 2 of the Electronic supplementary material. NAFLD, endothelial dysfunction, early carotid atherosclerosis and left ventricular dysfunction NAFLD is associated with circulatory endothelial dysfunction [16,17], a marker of early atherosclerosis. Compared with non-steatotic controls, non-diabetic patients with NAFLD show a significant decrease in brachial artery flow-mediated vasodilation, which is related to the severity of NAFLD histology, independently of age, sex, BMI and HOMA-IR [16].…”
Section: Evidence Linking Nafld With Cvdmentioning
confidence: 99%
“…19 In a study it was reported that the mean CIMT above 0.8 mm was associated with a higher prevalence of CAD. 20 Considering mean CIMT > 0.8 mm to be significantly associated with CAD, 43.47% NAFLD patients, 28.57% AFLD patients and 28.75% controls had CIMT >0.8 mm in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, there have been numerous reports about associations of NAFLD and increased CVD prevalence. In a study with a large sample of middle-aged male workers they found that people with NAFLD were more likely to have CVD than those without it, even more, the association was independent of obesity and other prognostic factors (Lin et al, 2005). Another study showed that the occurrence of NAFLD was significantly higher in subjects with acute myocardial infarction and also, that the severity of coronary artery disease was greater in these individuals independent of age, sex and BMI (Kessler et al, 2005).…”
Section: Associations Of Nafld and Atherogenesismentioning
confidence: 99%